Ecocide, genocide, capitalism and colonialism: Consequences for indigenous peoples and glocal ecosystems environments. (August 2018) - Crook, Martin; Short, Damien; South, Nigel
Continuing injustices and denial of rights of indigenous peoples are part of the long legacy of colonialism. Parallel processes of exploitation and injustice can be identified in relation to non-human species and/or aspects of the natural environment. International law can address some extreme examples of the crimes and harms of colonialism through the idea and legal definition of genocide, but the intimately related notion of ecocide that applies to nature and the environment is not yet formally accepted within the body of international law. In the context of this special issue reflecting on the development of green criminology, the article argues that the concept of ecocide provides a powerful tool. To illustrate this, the article explores connections between ecocide, genocide, capitalism and colonialism and discusses impacts on indigenous peoples and on local and global (glocal) ecosystems.